Ultra-Light Clay Intervention Improves Responsiveness and Initiates the Communication of Children With ASD - Zhang, Jing; Sun, Qingzhou; Liu, Xue; Yang, Fuyi (Frontiers in Psychology, 2022)
The barriers to responsiveness and the initiation of communication are the two key problems encountered by children with ASD. Prior interventions based on behavioral reinforcement have had an obvious effect on responsive communication but a weak effect on the initiation of communication. Based on psychological development theory, we designed Ultra-light Clay interventions, which involve hands-on production or multi-interaction around key concepts and themes, teaching children about basic concepts, relationships, and logic, making abstract knowledge concrete and experienced. Two studies (Study 1: one-to-one intervention; Study 2: one-to-two intervention) showed that ultra-light clay intervention improved both the initiation of and responsive to communication among children with ASD, but that such improvements show a peer-generalization effect in initiation communication, not in responsive communication. These findings provide a set of ultra-light clay interventions on communications for children with ASD and suggest a relation between endogenous interventions and the initiation of communication.